Stylocarotid syndrome: An unusual case report - Jayachandran Sadaksharam; Khushboo Singh (Wolters Kluwer Medknow Publications, 2012)
Patients presenting with vague head and neck pain can lead to wide-ranging differential diagnosis. Elongation of styloid process (SP) should also be considered as one of the etiological factors for cervical pain radiating to jaws, pharyngodynia, and difficulty in swallowing. Symptomatic elongation of SP or mineralization of stylohyoid ligament is referred as Eagle's syndrome. It is a rare entity presenting with an array of symptoms like recurrent throat pain, dysphagia, otalgia, and neck pain. History and physical examination play a vital role in diagnosing this condition and further radiological investigation confirms the diagnosis. The preferred radiologic modality is 3D-computed tomography, which gives accurate information about length, angulation, type of elongation, and relation to vital structures and hence helps in execution of treatment planning. This paper describes clinical approach, imaging investigations, and management of a case of Eagle's syndrome.